Mathematics Pocket book Market Research - Dhea Ika Felisa; Kiranasari, Shinta Puspa; Al Hawari, Defahayu As Syaura (Journal of Public Policy Analys, 2024)
Mathematics is a scientific discipline that plays a crucial role in developing skills and thinking that are important in everyday life. In mathematics learning, effective and practical learning resources are the determining factor for success in achieve learning goals. Answering this problem, the mathematics pocket book Handy Math: Math Made Simple from Elevateach Media is here as a potential solution. This research aims to obtain the results of analysis and interpretation of market research data regarding the potential and market interest in mathematics pocket book products. Worksheets are used to conduct market research to identify target consumers followed by establishing test hypotheses to determine the level of competency and business potential. The analytical method used is through trend, similarity, contradiction and odd groups analysis of data obtained through distributing questionnaires. Market research results stated that 67.9% of respondents had an attractive impression of mathematics pocket books. Pocket books are more widely known when attending school, so marketing pocket books to schools will increase sales. Mathematics pocket books need to pay attention to quality in terms of content/material, design and practicality of the pocket book. The most popular pocket book products are in the price range of IDR 20,000 - 30,000.